2007
DOI: 10.1086/512095
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Chemistry of the Hot Molecular Core in G34.26+0.15 at High Resolution

Abstract: We present high angular resolution ($1 00 ) multitracer spectral line observations toward the hot molecular core (HMC) associated with G34.26+0.15 between 87 and 109 GHz. We have mapped emission from (1) complex nitrogenand oxygen-rich molecules such as CH 3 OH, HC 3 N, CH 3 CH 2 CN, NH 2 CHO, CH 3 OCH 3 , and HCOOCH 3 ; (2) sulfurbearing molecules such as OCS, SO, and SO 2 ; and (3) the recombination line H53 . At this high resolution (0.018 pc) we find no evidence for the HMC being internally heated. The con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 54 publications
(141 reference statements)
11
75
1
Order By: Relevance
“…5); this shocked region and the tracer velocity are in agreement with the results of the study of SiO in Hatchell et al (2001). Their emitting region corresponds to a cometary CH II region, which is called C in the literature (Mookerjea et al 2007). Fig.…”
Section: G34supporting
confidence: 86%
See 1 more Smart Citation
“…5); this shocked region and the tracer velocity are in agreement with the results of the study of SiO in Hatchell et al (2001). Their emitting region corresponds to a cometary CH II region, which is called C in the literature (Mookerjea et al 2007). Fig.…”
Section: G34supporting
confidence: 86%
“…The cloud contains 1.1 × 10 4 M of dense gas (Hill et al 2005), and has a luminosity of 3.2 × 10 5 L (van der Tak et al 2013), with an age of a few × 10 4 yr (Paron et al 2009). From radio continuum observations, this source shows two very condensed UCH II regions (called A and B), a more evolved CH II region with a cometary shape (called C) and an extended ringlike H II region (called D) (Reid & Ho 1985;Mookerjea et al 2007). There are several outflows in G34, as evidenced by SiO emission extending to the north-west, south-east and north-east of the CH II region (Hatchell, Fuller & Millar 2001).…”
Section: Sourcesmentioning
confidence: 99%
“…Chemical differentiation in hot cores has been observed before (Mookerjea et al 2007;Garay & Lizano 1999) and attributed to either differences in their host star mass and/or differences in ages. Results of chemical models in the past have suggested that determining abundance ratios of typical hot core tracers (e.g.…”
Section: Spectral Modellingmentioning
confidence: 99%
“…Several components have been identified in radio continuum observations: two ultra compact HII regions called A and B, a more evolved HII region with a cometary shape (component C), and an extended (1 ) HII region (component D) in the south-east. Chemical surveys were carried out towards the A, B and C components using single-dish telescopes (MacDonald et al 1996;Hatchell et al 1998) and interferometric observations (Mookerjea et al 2007). Many complex species, characteristic of hot cores, have been detected.…”
Section: Source Descriptionmentioning
confidence: 99%
“…Many complex species, characteristic of hot cores, have been detected. From molecular line observations, the emission peak does not coincide with the HII components (Watt & Mundy 1999;De Buizer et al 2003), but is shifted to the East of the component C by ∼1 (Mookerjea et al 2007: Figure 3). This difference may arise due to the external influence of the nearby HII regions, or may reveal separate regions of chemical enrichment.…”
Section: Source Descriptionmentioning
confidence: 99%